Application of Competitive Activities to Improve Students' Participation - Francisco, Virginia; Moreno-Ger, Pablo; Hervás, Raquel (IEEE Transactions on Learning Technologies, 2023)
Making students become intrinsically motivated to participate in daily class activities is an open challenge that has been addressed in different ways. In this article, we evaluate the impact of an educational innovation project, named TrivialCV, in terms of student motivation, engagement, and learning outcomes. We analyze the impact of two types of activities: multiplayer team-based competitions created for delivery during a live class session and single-player competitions created to be played asynchronously from home. We deployed these activities in two different computer engineering courses (programming fundamentals and operating systems) and used questionnaires, grades, and activity tracking in the virtual campus to evaluate their impact. After the analysis, we can assert that the use of TrivialCV activities was useful for providing additional motivation to the students and improving their engagement with the courses in which they were deployed. TrivialCV activities were very well received by the students, who considered them fun, engaging, and useful.
Keywords: games; education; collaboration; programming profession; technological innovation; operating systems; electronic learning; competitive and collaborative learning experiences; engagement; learning outcomes; motivation; participation; single-player activities; team-based competition activities; JCR; Scopus